Are patients with bipolar disorder and comorbid attention‐deficit hyperactivity disorder more neurocognitively impaired?. (21st September 2017) - Torres, Imma; Sole, Brisa; Corrales, Montse; Jiménez, Esther; Rotger, Sofia; Serra‐Pla, Juan Francisco; Forcada, Irene; Richarte, Vanesa; Mora, Ester; Jacas, Carlos; Gómez, Nuria; Mur, Maria; et al.
Abstract : Objective: Research on neurocognitive impairment in adult patients with comorbid bipolar disorder (BD) and attention‐deficit hyperactivity disorder (ADHD) is very scarce. This study assessed the neurocognitive profile of a comorbid group (BD+ADHD) compared with that of pure BD (pBD) group, pure ADHD (pADHD) group and healthy controls (HCs). Methods: This was a three‐site study comprising 229 subjects: 70 patients with pBD, 23 with BD+ADHD, 50 with pADHD, and 86 HCs. All patients with BD had been euthymic for at least 6 months. Neuropsychological performance was assessed using a comprehensive neurocognitive battery. Results: Our results showed that all the clinical groups had poorer performance than the HCs in all the neurocognitive domains except for executive functions. No significant differences were observed between the pBD and BD+ADHD groups in any of the cognitive domains, with these two groups showing greater impairment than the pADHD group in executive functions and visual memory. Conclusions: Our results, although preliminary, suggest that the BD+ADHD group showed the same neurocognitive profile as pBD patients, most likely reflecting the same neurobiological basis. On the other hand, the pADHD group showed a more selective moderate impairment in attention.